Mapping the Landscape of Fiscal Discipline: A Four-Decade Bibliometric Analysis of Global Scholarship (1981–2024) - Andriansyah, Yuli; Atmaja, Fajar Fandi; Lana, Rima Isfah; Azmi , Ghitha Nabilah; Mešković, Admir (Unisia, 2025)
Fiscal discipline remains a critical pillar in ensuring macroeconomic stability and responsible public finance management, particularly amid recurring global economic crises. This study aims to systematically map the intellectual landscape of fiscal discipline research using bibliometric analysis to uncover publication trends, thematic developments, and scholarly networks from 1981 to 2024. Drawing upon data from the Scopus database, the study analyzed 688 academic documents using performance analysis and science mapping techniques. Tools such as VOSviewer were employed to visualize co-authorship, co-citation, and keyword co-occurrence networks, enabling the identification of influential authors, institutions, and thematic clusters. The results reveal a sharp increase in research activity post-2000, largely driven by financial disruptions such as the Eurozone crisis and the COVID-19 pandemic. The literature is dominated by contributions from developed countries and international institutions, with limited representation from developing regions. Seven thematic clusters were identified, including fiscal rules in the European Union, subnational fiscal discipline, transparency and governance, and the political economy of fiscal policy. These findings reflect a shift from rules-based approaches toward broader frameworks that incorporate institutional credibility, political context, and adaptability. This study contributes to the advancement of fiscal discipline research by providing a comprehensive, data-driven overview of its evolution, gaps, and interdisciplinary intersections. It highlights the need for more inclusive, context-sensitive studies, particularly from underrepresented regions. The findings offer a foundation for future inquiry and inform more effective and equitable fiscal governance in an increasingly complex global environment.